Determining the vulnerabilities of wireless LAN (WLAN) in educational environment - Ahmad, Amran; Daud, Ali Yusny; Azzali, Fazli (Universiti Utara Malaysia, 2008)
The advancement and proliferation of wireless local area network nowadays have driven for an alarm on the whole network operation.The concern applies to both business and academic computer network environments.This report describes our research and experiences in performing network vulnerabilities analysis in academic local area network.The research uses network vulnerability analysis methodology to perform vulnerability analysis on Academic and Administration building.From the analysis, the overall network security level was determined.During WArDriving session, a few important factors had been found such as a number of Access Point (AP) and ad-hoc client were not used any security method and several used default SSID.Remedies and solution to counter the vulnerability also prescribed such as any Rogue Access Point discovered should be eliminated, educate users not to plug-in any AP without permission and also proper configuration, and use authentication control access to each AP that setup legally in LAN.Hopefully, this will reduce network vulnerability threat to academic LAN.